ICHTYOFAUNA AT CIJALU RIVER, CILACAP REGENCY CENTRAL JAVA PROVINCE, INDONESIA - Agus Nuryanto; Dian Bhagawati; M Nadjmi Abulias; Indarmawan Indarmawan (Biotropia: The Southeast Asian Journal of Tropical Biology, 2016)
Cijalu River is located in Western Cilacap Regency of Central Java Province. The river runs through forestry, housing and farming areas. This condition leads to a prediction that the river has been altered on its physico-chemical characteristics causing the river to be inhabited by a variety of fish species. This study aimed to collect data about fish species inhabiting Cijalu River and its distribution. A survey method has been done with clustered random sampling technique. The river was divided into three different areas, i.e. upper-, middle- and downstreams. Species diversitywas measured as the number of species, while distribution was measured as the presentation of fish species in each site. Nineteen fish species of 10 families were identified from Cijalu River. The 10 families were Anabantidae, Bagridae, Balitoridae, Channidae, Cichlidae, Cyprinidae, Loricariidae, Osphronemidae, Poecilidae and Sisoridae. Cyprinidae was the family having the highest number of species (6 species), followed by Bagridae (3 species), Channidae (2 species) and Osphronemidae (2 species). The remaining respective families were represented by one species. A complex pattern of fish distribution was observed during the study. Glyptothorax platypogon and Channa gacua were only found at the upper-streams, while Anabas testudineus was obtained in downstreams. The other remaining species could be observed either from the middle-to downstreams, or even from upper- to downstreams. Different pattern of species distribution could be caused by physico-chemical characteristics variation from upper to lower parts of the river, especiallywater velocity and substrate types.